The Financial Rewards of New Product Introductions in the Personal Computer Industry - Bayus, Barry L.; Erickson, Gary; Jacobson, Robert (Management Science, 2003)
Based on data from firms in the personal computer industry, we study the effect of new product introductions on three key drivers of firm value: profit rate, profit-rate persistence, and firm size as reflected in asset growth. Consistent with our theoretical development, we find that new product introductions influence profit rate and size; however, we find no effect on profit-rate persistence. Interestingly, we also find that the effect of new product introductions on profit rate stems from a reduction in selling and general administrative expenditure intensity rather than through an increase in gross operating return. Notably, firms decrease their advertising intensity in the wake of a new product introduction. Firm profitability in this industry apparently benefits from new product introductions because new products need less marketing support than older products.